Psychological distress as a mediator between work family conflict emotional exhaustion and job embeddedness - Jayendira P. Sankar (Discover Psychology)
Abstract In the modern workplace, the private banking sector is facing increased regulatory demands, intense competition, rising workloads, and heightened work-related stress. This study explores the dynamics among bidirectional work-family conflict, emotional exhaustion, psychological distress, and job embeddedness. To underpin the hypothesized relationships, the study draws on the Conservation of Resources (COR) Theory, the Job Demands-Resources (JD-R) Model, and the Affective Events Theory (AET). The study used quantitative analysis of cross-sectional data collected from 498 employees of private commercial banks in India across management levels, and the data were analyzed using partial least squares structural equation modeling (PLS-SEM). The results highlight that bidirectional work-family conflict and emotional exhaustion negatively influence job embeddedness, both directly and indirectly, through psychological distress. The findings highlight actionable insights and theoretical advancements in organizational retention strategies by private commercial banks, aiming to enhance employee well-being and address work stressors through a resource-centric approach. This study fills a notable gap by examining these relationships within an underexplored context, providing a robust foundation for future investigations into employee dynamics in high-pressure environments.